2021
DOI: 10.1097/shk.0000000000001727
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Converting Asystole From Initial Shockable ECG Rhythm Before Extracorporeal Cardiopulmonary Resuscitation and Outcome

Abstract: Background: Initial electrocardiogram (ECG) rhythm is a predictor of outcomes in out-of-hospital cardiac arrest (OHCA) in patients receiving extracorporeal cardiopulmonary resuscitation (ECPR). However, ECG rhythm often changes before ECPR, and the consequence of this change remains unclear. This study aimed to assess the relationship between the conversion of ECG rhythm from initial shockable rhythm before ECPR and mortality. Patients and Methods: This was a retrospective cohort study of OHCA patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This happened either before arrival of HEMS, in the presence of HEMS, or on route to hospital (if conveyed). Previous studies have demonstrated that this is a poor prognosticator when ECPR is initiated, 25 and therefore asystole on presentation is often regarded as a contraindication. The relatively high number of patients with a rhythm conversion is most likely the result of the prolonged travel times.…”
Section: Discussionmentioning
confidence: 99%
“…This happened either before arrival of HEMS, in the presence of HEMS, or on route to hospital (if conveyed). Previous studies have demonstrated that this is a poor prognosticator when ECPR is initiated, 25 and therefore asystole on presentation is often regarded as a contraindication. The relatively high number of patients with a rhythm conversion is most likely the result of the prolonged travel times.…”
Section: Discussionmentioning
confidence: 99%
“…Based on meta-analyses and observational studies, an initial shockable cardiac rhythm is considered a major prognostic factor for favorable neurologic outcomes for OHCA patients [12]. In addition to initial cardiac rhythm following OHCA, shockable cardiac rhythm upon ECPR initiation was associated with favorable neurological outcome at hospital discharge while conversion to asystole (from an initial shockable rhythm) before ECPR initiation was associated with increased mortality [13 ▪ ].…”
Section: Whomentioning
confidence: 99%
“…In consideration of the diverse indications of both therapeutic approaches, it is feasible to achieve the desired therapeutic efficacy on PCAS by selecting appropriate therapy tailored to the cause of CA. Unfortunately, identifying the etiology of CA in a prehospital setting is difficult because the emergency medical service response time is usually more than 8 minutes, during which the initial rhythms of asphyxia and dysrhythmia may have changed spontaneously (12,13). Therefore, a universally effective treatment for CA with unknown etiology is of great need to solve the difficulty of indistinguishability of asphyxial and dysrhythmic CA in comatose patients.…”
Section: Introductionmentioning
confidence: 99%